REPRESENTATION OF PSYCHOPHYSIOLOGICAL STATES CONVEYED THROUGH INTONATION - Manzura Shokirjon qizi Abdurahimova (Modern American Journals, 2025)
This article explores the role of intonation in literature as both a linguistic and psychophysiological phenomenon. Drawing on theoretical perspectives of scholars such as N.G. Chernyshevsky, A.S. Makarenko, Umarali Normatov, I. Rustamova, Farmanovsky, and V. Zhinkin, the study highlights how intonation functions in literary narratives as a marker of psychological depth, emotional resonance, and aesthetic wholeness. Through the analysis of Abdulla Qahhor’s short stories and Nabi Jaloliddin’s novella The Color of Death, the article demonstrates how intonation transcends verbal expression, shaping character portrayal and revealing inner psychological states.
Keywords: Intonation, psychologism, paralinguistics, psychophysiological state, literary analysis, artistic integrity, Uzbek literature, Nabi Jaloliddin, Abdulla Qahhor